Pengaruh Model Picture and Picture Berbantuan Quizizz Paper Mode Terhadap Motivasi dan Hasil Belajar IPAS Siswa SD - Noviyanti, Titik; Rukmana, Diki (BRILIANT: Jurnal Riset dan Konseptual, 2025)
The objective of this study is to determine the extent to which the utilization of the picture and picture learning model, with the assistance of Quizizz Paper Mode, impacts the motivation and science learning results of elementary school children. The use of conventional teaching and learning models and less interactive media results in low student learning motivation at the teaching and learning stage, and as a result, learning outcomes are less than optimal. This study utilized a quasi-experimental approach, specifically employing a posttest-only control group design. We processed the data using: 1) descriptive statistics; 2) normality tests; 3) homogeneity; 4) t-test hypotheses, and effect sizes. The results of the t-test on learning motivation indicate that tcount (4.742) surpasses ttable (2.010), whereas the t-test on learning outcomes reveals that tcount (2.753) surpasses ttable (2.010), leading to the acceptance of Ha and the rejection of Ho. The effect size test reveals a significant impact, specifically a significant increase in learning motivation (d = 1.341) Furthermore, there was a notable enhancement in learning outcomes, with an effect size of 0.778. Thus, we may infer that implementing this instructional model has an impact on the motivation and learning outcomes of elementary school students of IPAS subjects.